Interstitial Pregnancy a Rare form of Ectopic Pregnancy: Case Report - Mohannad AbuFaza; Ibrahim A. Abdelazim (Medical Network, 2018)
Interstitial pregnancy is a rare variety of ectopic pregnancy, it can have disturbed 8-16 weeks of amenorrhea (later than the distal tubal ectopic pregnancy), due to the dispensability of the myometrium covering the interstitial segment of the fallopian tube, with subsequent massive internal hemorrhage. A 29-years-old female, Gravida 3, Para 2, presented with severe abdominal pain, vomiting, and syncope 3 days after her missing period, and positive pregnancy test. Trans-vaginal ultrasound showed empty uterine cavity, free pelvic fluid with severe cervical motion tenderness. She was diagnosed with ruptured ectopic pregnancy. Ruptured ectopic pregnancy in the proximal segment of right fallopian tube was confirmed with laparotomy. The ruptured pregnancy was managed by right salpingectomy, and hemostatic stitches at the right uterine corn. Her hemoglobin was 8 gr on admission, and she received 3 units of packed RBCs (one intra-operative, and two post-operative). Her post-operative hemoglobin was 10.5 gr, and she was discharged from the hospital on the 3rd post-operative day in good general condition for follow up in the outpatients` department. This case report represents a rare variety of ectopic pregnancy, which is the interstitial pregnancy, because it can rupture few days or weeks after the missed period with subsequent massive internal hemorrhage. Interstitial pregnancy is a rare form of ectopic pregnancy, the obstetricians should be aware of rare forms of ectopic pregnancies, it can have disturbed few days or weeks after the missed period leading to subsequent significant morbidity.